Another epidemic: abuse and violence towards doctors from patients and the public. (24th March 2021) - Oxtoby, Kathy
Abstract : In the context of covid-19, persistent abuse of NHS doctors compounds the emotional toll on staff, damages morale, and threatens patient safety. Plans to stem the tide may be insufficient, as Kathy Oxtoby reports